Immigration and Entrepreneurship in Texas: Chronicle of an Experience (1995-2010) - Treviño Garza, Edmundo (Libros UANL, 2023)
This is a book I never dreamed of writing. After emigrating from Mexico to the United States and undertaking, in total ignorance of the Texas market, a family own business in which I have been able to try every idea that has come to my mind, with total creative and innovative freedom but with resource restrictions and a lot of entrepreneurial ignorance, my family and I have been able to overcome countless obstacles to bring to fruition a number of small and medium-size businesses.The Covid-19 pandemic forced me to pause and reflect on all the lessons accumulated over 20 years, dozens of projects and multiple partnerships, which, when put in a short text, forced me to share the knowledge to other entrepreneurs in social networks and then, to write this book.